The Effect of Comparison of Soybeans and Coconut Water on Bio-Battery Electrical Power - Valensia, Valensia; Sadiyyah, Fitriani Halimatus; Hibatulloh, Miussa Rio; Setiadi, Dwi Putra; Nandiyanto, Asep Bayu Dani; Anggraeni, Sri; Kurniawan, Tedi (Indonesian Journal of Multidiciplinary Research, 2021)
The world is currently facing an energy crisis. This research was conducted to create alternative energy by utilizing abundant biomass in nature. The novelty of this study: (1) Use of soybean biomass with coconut water as an electrolyte paste, (2) Testing of bio-battery resistance to wall clocks, and (3) Comparison of the composition of the two materials. In this study, an electrolyte paste made from soybeans (SBs) and coconut water (CWs) with a ratio of 7/1, 6/2, 5/3, 4/4, 3/5, 2/6, and 1/7. To support the analysis, an electrical voltage test and a battery resistance test for wall clocks were carried out.Â  The experimental results show that the composition of coconut water increases the value of the electric voltage on the bio-battery. The composition of coconut water serves to activate the ions in the paste. Meanwhile, more soybean content will increase bio-battery life. It was found that the bio-battery with electrolyte paste of soybeans and coconut water can be used as alternative energy. The results of this research are expected to offer renewable alternative energy for world energy security.